2011
DOI: 10.4161/viru.2.2.15337
|View full text |Cite
|
Sign up to set email alerts
|

<span style=" font-size

Abstract: We described an association between a strain of the nematode Caenorhabditis briggsae, i.e. KT0001, and the bacteria Serratia sp. SCBI (South African Caenorhabditis briggsae isolate), which was able to kill the insect Galleria. Here we show that the Serratia sp. SCBI lines the gut of the nematode, similar to the Heterorhabditis-Photorhabdus complex, indicating that the association is possibly internal. We also expand on the relevance of this tripartite, i.e. insect-nematode-bacteria, interaction in the broader … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…marcescens (including the type strain), and two genomes of other Serratia species. Interestingly, the closest genome match (98.49% similarity, as shown by AAI identity scores listed in the S1 Dataset) of Ss1 is to Serratia sp SCBI [31,32], a pathogen of the lepidopteran Galleria mellonella (honey comb moth), which is a pest of honey bee colonies. The complete dendrogram that includes the phylogenetic relationships of all 42 Serratia genomes based on AAI analysis is also provided as an unrooted phylogenetic tree (S2 Fig), and their distance scale values are shown in S1 Dataset.…”
Section: Resultsmentioning
confidence: 99%
“…marcescens (including the type strain), and two genomes of other Serratia species. Interestingly, the closest genome match (98.49% similarity, as shown by AAI identity scores listed in the S1 Dataset) of Ss1 is to Serratia sp SCBI [31,32], a pathogen of the lepidopteran Galleria mellonella (honey comb moth), which is a pest of honey bee colonies. The complete dendrogram that includes the phylogenetic relationships of all 42 Serratia genomes based on AAI analysis is also provided as an unrooted phylogenetic tree (S2 Fig), and their distance scale values are shown in S1 Dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Differential gene expression was calculated by normalizing the data utilizing the trimmed mean of M-values normalization method and filtering out genes that had <10 counts per million (CPM) within the edgeR package (35). Statistical analysis was performed in RStudio (v 0.98.1102) (36) by the exact test with a negative binomial distribution for each set of conditions and testing for differential gene expression using edgeR (35). Differentially expressed genes were determined to be statistically significant based on an adjusted p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…2009; Abebe et al. 2011). However, genome characterization of these two species revealed that their genome characteristics are similar to those non-host-restricted Serratia , with a chromosome that is >5 Mb in size, 55%–60% GC and containing >4500 CDSs (Taira et al.…”
Section: Recent Progress In Facultative Insect Symbiontsmentioning
confidence: 99%